Acute resistance to BET inhibitors remodels compensatory transcriptional programs via p300 coactivation - Shah, Viral Virendra; Giotopoulos, George; Osaki, Hikari; Meyerhöfer, Markus; Meduri, Eshwar; Gallego-Crespo, Aaron; Behrendt, Malte A.; Saura-Pañella, Maria; Tarkar, Aarti; Schubert, Benedict; Yun, Haiyang; Horton, Sarah J.; et al. (Blood, 2025)
Initial clinical trials with drugs targeting epigenetic modulators, such as bromodomain and extraterminal protein (BET) inhibitors, demonstrate modest results in acute myeloid leukemia (AML). A major reason for this involves an increased transcriptional plasticity within AML, which allows the cells to escape therapeutic pressure. In this study, we investigated the immediate epigenetic and transcriptional responses after BET inhibition and demonstrated that BET inhibitor-mediated release of bromodomain-containing protein 4 from chromatin is accompanied by acute compensatory feedback that attenuates downregulation or even increases the expression of specific transcriptional modules. This adaptation is marked at key AML maintenance genes and is mediated by p300, suggesting a rational therapeutic opportunity to improve outcomes by combining BET and p300 inhibition. p300 activity is required during all steps of resistance adaptation; however, the specific transcriptional programs that p300 regulates to induce resistance to BET inhibition differ, in part, between AML subtypes. As a consequence, in some AMLs, the requirement for p300 is highest during the earlier stages of resistance to BET inhibition, when p300 regulates transitional transcriptional patterns that allow leukemia-homeostatic adjustments. In other AMLs, p300 shapes a linear resistance to BET inhibition and remains critical throughout all stages of the evolution of resistance. Altogether, our study elucidates the mechanisms that underlie an “acute” state of resistance to BET inhibition, achieved through p300 activity, and how these mechanisms remodel to mediate “chronic” resistance. Importantly, our data also suggest that sequential treatment with BET and p300 inhibition may prevent resistance development, thereby improving outcomes.
Online verfügbar 9 December 2024, Version des Artikels 13 February 2025
Gesehen am 31.07.2025